Molecular Epidemiology of Coronavirus Disease and its Effect on the Hematological Profile in District Kech, Balochistan: Effect of the Coronavirus Disease on the Hematological Profile - Niamatullah Kakar; Talal Qadir; Zameera Wahid; S. Sameera Khan; Ghulam Nabi; Zalia Majeed; Irfan Shahzad Sheikh; Habib Ur Rehman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The coronavirus disease (COVID-19) is a respiratory disease caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). This study aimed to investigate the occurrence of COVID-19 in district Kech, associated risk factors, clinical presentation, and its effect on blood cells. A structured questionnaire was designed to collect the data and the samples were investigated by RT-PCR. In total, 575 suspects were screened, among which 64 (11.16%) had COVID-19 infection, 40.6% were males, and 59.4% were females. An increased positivity of 53.12% was measured in the younger age group (15-30 years) and the lowest (18.75%) was noticed in elders > 50 years. 95.3% of the patients were newly infected, and 7.7% had a contact history with COVID-19-infected patients. The clinical symptoms, such as fever, cough, nausea, vomiting, and diarrhea, were identified in 89.1%, 67.2%, 51.6%, 46.9%, and 12.5%, respectively. The prominent clinical features, like fever, cough, nausea, diarrhea, chest distress, chest pain, and psychological stress were observed. Noticeably, 10.9% of obesity and 7.8% of asthma patients were co-infected with COVID-19 disease including 39.1% of cases showed psychological trauma. Leucocytosis and a decrease in hemoglobin concentration and platelets were determined in COVID-19-infected patients. A significant effect was observed on the hematological profile, however, the effect was severe in the older age group (>50 years). The results suggest that the large population of the study area is infected by SARS-CoV-2, appealing to the need for surveillance on a large scale and the implementation of preventive measures to control further dissemination of the disease.